RESEARCHING OF THE ADSORPTION PROCESS OF TEXTILE DYES ON THE SURFACE OF NATURAL SORBENT ZEOLITE - KOVAL, MYROSLAVA; KUZMENKO, VLADYSLAV; ROMANENKO, NATALIYA; FESHCHENKO NATALIІA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A large amount of dyes from various industries end up in wastewater and subsequently in natural water bodies. This poses a high risk to the aquatic environment due to a decrease in oxygen concentration. Adsorption is one of the most common methods of cleaning wastewater from dyes due to the low cost and high efficiency of the process. The paper investigates the processes of adsorption absorption of textile dyes of different classes (reactive, direct and dispersed) from their aqueous solutions using natural zeolite from the Sokyrnytsia deposit (Ukraine), which has undergone preliminary thermal modification and chemical activation. The kinetics of the process and the rate of saturation of the sorbent with dyes were determined during experimental studies on a bench unit with a mechanical stirrer. It was established that the solution reaches equilibrium concentrations in 40-60 minutes from the beginning of contact, depending on the class of dye, and the efficiency of dye absorption by the sorbent is 70-90%. In order to determine the physicochemical basis of the sorption process, adsorption isotherms were constructed by the graph-analytical method, which confirm the typical microporous structure of zeolites by the nature of curvature and convexity. The practical efficiency of sorption is confirmed by theoretical calculations and the description of the process by the Langmuir and Freundlich models. It was determined that the adsorption of textile dye molecules by zeolite is carried out both according to Langmuir (R2 = 0.98) and Freundlich (R2 = 0.99). The Freundlich isotherm provides a better fit and is more applicable to the process of dye sorption by zeolite, since the reliability coefficient has higher values (R2 = 0.99). The value of free energy (Gibbs energy) was determined and the possibility of using zeolite for dye sorption was confirmed thermodynamically.